DLH and WALHI's Perception of the Local Wisdom Values of Pasang Ri Kajang as an Environmental Conservation Effort - Sabriani; Syukri; Syahban Nur; Arafi Gunawan; Isti Anna (Faculty of Law, Universitas Pekalongan, 2025)
This study aims to examine the perceptions of the Environmental Office (DLH) and the Indonesian Forum for the Environment (WALHI) regarding the local wisdom values of Pasang Ri Kajang in the context of environmental conservation efforts in Bulukumba Regency, South Sulawesi. A qualitative approach was employed, utilizing a case study method, which involved in-depth interviews, participatory observation, and documentation with key informants from DLH, WALHI, and indigenous Kajang leaders. The findings reveal that both DLH and WALHI hold positive perceptions of Pasang Ri Kajang, particularly in terms of forest preservation, sustainable natural resource management, and the spiritual relationship between humans and nature. These values are perceived to align with modern ecological principles and serve as an alternative foundation for policy formulation in conservation efforts. The study also highlights institutional and sectoral challenges in integrating local values into environmental programs. Therefore, synergy among state actors, civil society organizations, and indigenous communities is essential to mainstreaming local wisdom into sustainable environmental policies.